Henoch–Schönlein purpura – obravnava in zdravljenje pediatričnih bolnikov severovzhodnega dela Slovenije: Henoch–Schönlein purpura – obravnava in zdravljenje slovenskih pediatričnih bolnikov severovzhodnega dela Slovenije - Močnik, Mirjam; Marčun Varda, Nataša (Acta Medico-Biotechnica, 2022)
Purpose: Henoch–Schönlein purpura (HSP) is the most common type of vasculitis in childhood and has a good prognosis. The aim of our study was to compare the clinical characteristics of children with HSP diagnosed in north–east Slovenia with existing data from other countries.Methods: We retrospectively reviewed the data of patients with HSP in our department between 2005 and 2018, and assessed their clinical characteristics, laboratory results, and treatment at presentation. We also analysed how many patients relapsed, the causes of this, and the treatment administered. These parameters were compared with previously published research.Results: During the study period, 123 patients with HSP were treated in our department. The median patient age was 6.0 years (interquartile range: 4–9 years) with a uniform distribution between the sexes. Along with purpura, 52.8% presented with arthropathy, 19.5% with abdominal pain, and up to 10% with renal involvement. Patients received supportive therapy the most frequently. Non–steroidal anti–inflammatory drugs were prescribed to 61.8% of patients and corticosteroids to 13%. Relapse occurred in 15.4% of patients, most presenting with skin purpura and kidney manifestations.Conclusion: The basic demographic data of our patients were comparable to those of other similar published studies. The order of frequency of individual organ system involvement was also similar, but the percentages were lower. Purpura–accompanying manifestations were reported less often in our study than in previous studies. Compared to other studies, supportive therapy alone was prescribed more frequently to our patients, and corticosteroids were rarely administered. Compared to other studies, a smaller proportion of patients with relapse was recorded.
Keywords: Henoch–Schönlein purpura, epidemiology, clinical picture, management, children